Authorship and Nostalgia in Contemporary Cowboy Repertoire. (February 2016) - Turnbull, Gillian
The genre of cowboy music, first developed by working cowboys in the late 19th and early 20th centuries, has been thoroughly documented by early folklorists, and revived by younger performers working as professional songwriters. Through an analysis of the cowboy classics recorded by Ian Tyson, and of six volumes of cowboy songs available in written form, this article proposes that despite the weight of tradition that cowboy repertoire bears, it has been one that favors new composition because it exists as a folk music, a commercial music, and an art music all at once. This article will also consider the significant role of place in Western song; for cowboy singers, the ongoing disappearance of an old West is a source of both despair and inspiration. In this sense, songwriters are not only responsible for creating a picture of a mythic West but also charged with reminding listeners that it should still exist, thereby shaping our knowledge and experience of the region through song. The resurrection of old repertoire is one of the ways cowboy singers can respond to anxiety over the vanishing West. These songs, alongside new compositions that maintain sentimentality for the past, serve a nostalgic function for audiences who long for a lost West but have never experienced it as it is portrayed in art.